1982
DOI: 10.1111/j.1752-1688.1982.tb03967.x
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMIC EVALUATION OF WATERSHED PROJECTS ‐ AN OVERVIEW METHODOLOGY AND APPLICATION1

Abstract: Deforestation and intensive land use on a global scale has resulted in watershed deterioration and threatened municipal and irrigation reservoirs. Watershed rehabilitation programs must allocate funds to priority projects. A tool for decisionmakers is presented which provides a four-step overview economic analysis by the integration of physical and biological considerations. The overview tool is applied to a current proposed watershed project in Morocco. (KEY TERMS: watershed rehabilitation; economics; project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This study illustrates a practical approach to assessing the economic performance of a watershed management program in the Beijing municipal area. As with similar studies in Morocco (Brooks et al, 1982) and Taiwan (Wang et al, 1998), the methodology of Gregersen et al (1987) proved useful. As with these previous studies, the economic appraisal of watershed management practices indicated that they were economically viable and should be sustained.…”
Section: Discussionmentioning
confidence: 72%
“…This study illustrates a practical approach to assessing the economic performance of a watershed management program in the Beijing municipal area. As with similar studies in Morocco (Brooks et al, 1982) and Taiwan (Wang et al, 1998), the methodology of Gregersen et al (1987) proved useful. As with these previous studies, the economic appraisal of watershed management practices indicated that they were economically viable and should be sustained.…”
Section: Discussionmentioning
confidence: 72%
“…The analysis requires conversion of the weight of the sediments to volume and the speci® c weight of 1.5 t/m 2 was used in this conversion. This value is taken from Brooks et al (1982) and is near the average value of the Sri Lankan estimates of 1.72± 0.75 (CECB, 1978) and 1.98 (NEDECO, 1984). A linear relationship was assumed between sediment deposits and reduction of live storage capacity.…”
Section: Estim Ation Of Cost Of Sedime Ntationmentioning
confidence: 73%
“…In contrast, studies conducted on lowland and hot lowland agroecologies (Benishangul and SNNP) covered only small areas (6.4%), as indicated in Figure 3. This is because the focus of these areas is not on soil erosion, but rather on water conservation by constructing water‐harvesting dams and reservoirs for domestic, irrigation, and livestock consumption (Brooks & Tayaa, 2003).…”
Section: Discussionmentioning
confidence: 99%